VKORC1 and CYP2C9 genotypes in Egyptian patients with warfarin resistance. Issue 2 (March 2016) - Azzam, Hanan; Elwakeel, Hossam; Awad, Ibrahim; El-Farahaty, Reham; El-Gilany, Abdel-Hady; El-Sharawy, Solafa
Abstract : Warfarin is the most commonly prescribed anticoagulant drug; however, a narrow therapeutic range and a high risk of bleeding or stroke complicate its clinical use. Warfarin resistance was defined as prolonged warfarin requirements of more than 15 mg/day to achieve therapeutic anticoagulation or failure to achieve therapeutic anticoagulation with more than 20 mg/day. The resistance is associated with polymorphisms of the vitamin K epoxide reductase-oxidase complex ( VKORC1 ) and cytochrome P450-2C9 ( CYP2C9 ) genes, which affect warfarin pharmacodynamics and pharmacokinetics, respectively. Identification of the VKORC1 −1639 (A/G) and CYP2C9 (*1/*2/*3) allelic variants was performed using the PGX-Thrombo Strip in 41 patients with warfarin resistance compared with 30 patients with normal warfarin response out of 352 diagnosed cases of deep vein thrombosis. In warfarin-resistant patients, the VKORC1-1639 genotype frequencies were GG 0.756, GA 0.244 and AA 0.0, whereas in warfarin responder patients, they were: GG 0.333, GA 0.400 and AA 0.276 with P  ⩽ 0.001. The CYP2C9 genotype frequencies showed nonsignificant difference in both group of patients ( P  = 0.31). Our results suggest that the VKORC1−1639 GG and the wild type CYP2C9*1*1genotypes are associated with the high-dose requirement for warfarin therapy, and that VKORC1−1639 GG is responsible for warfarin resistance and failure in Egyptian patients.